Measurement of the [chi] b(3P) mass and of the relative rate of [chi] b1(1P) and [chi] b2(1P) production - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Journal of high energy physics, 2014)
The production of χbmesons in proton-proton collisions is studied using a data sample collected by the LHCb detector, at centre-of-mass energies of √s=7 and 8 TeV and corresponding to an integrated luminosity of 3.0 fb−1. The χbmesons are identified through their decays to ϒ(1S)γ and ϒ(2S)γ using photons that converted to e+e− pairs in the detector. The relative prompt production rate of χb1(1P) and χb2(1P) mesons is measured as a function of the ϒ(1S) transverse momentum in the χbrapidity range 2.0 < y <4.5. A precise measurement of the χb(3P) mass is also performed. Assuming a mass splitting between the χb1(3P) and the χb2(3P) states of 10.5 MeV/c2, the measured mass of the χb1(3P) meson is
Im Titel ist "chi" als griechischer Buchstabe dargestellt
Gesehen am 09.07.2020